SPECIFIC CHARACTERISTICS OF WORDS AND NEOLOGISMS IN UZBEKI AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2024)
In this article, the specific features of the borrowed words and neologisms in the Uzbek and English languages are studied. Since the first years of independence, Uzbekistan has paid great attention to the education system. Among them, he established relations with foreign countries and began to study their language, culture, and art. It was mentioned that the requirement for adopted neologisms is that they have one meaning, that they form a separate weighty layer in the lexical complex of the language.